INVASI UDANG AIR TAWAR Macrobrachium lanchesteri DI DANAU BOLANO TOGA, TOLI-TOLI, SULAWESI TENGAH - Annawaty, Annawaty; Safira, Safira (Biology Department, Mathematics and natural science, Tadulako University, 2023)
Sulawesi Island has long been known as one of the regions in Indonesia that holds a wealth of freshwater shrimp species in both lentic and lotic waters. One of the lentic waters in Sulawesi is Lake Bolano Tago which is located in Toli-Toli Regency, Central Sulawesi. This research aims to reveal the population and abundance of freshwater shrimp in the lake. Sampling was carried out in April 2022 along the lake's littoral zone which was divided into 7 stations using purposive sampling and sweep methods. Sampling effort at each station was carried out for 4 hours. Environmental physicochemical factors measured include water temperature, brightness, dissolved oxygen levels, and water acidity levels. Specimen identification was carried out at the Animal Biosystematics and Evolution Laboratory, Biology Department, FMIPA, Tadulako University. Identification was carried out based on morphological characters by following the identification key of Wowor et al (2004). The results of this research revealed that of the freshwater shrimp collected as many as 1,165 individuals in the lake, all consisted of one species, namely Macrobrachium lanchesteri. This species belonging to the Palaemonidae family is not native to Indonesia but comes from the Oriental region. Macrobrachium lanchesteri was first described based on a type specimen originating from Thailand. Its presence in Lake Bolano Toga is quite worrying because of its invasive nature. With the abundant presence of the M. lanchesteri species at all stations, it can be confirmed that the Macrobrachium lanchesteri species has invaded Lake Bolano Toga